2016
DOI: 10.1139/cjfas-2015-0444
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the influence of salinity and temperature on the population dynamics of a marine ectoparasite

Abstract: 1Sea lice are common ectoparasites of farmed and wild salmonids and can cause substantial 2 morbidity and mortality in their hosts. While sea lice infections are common in estuarine areas with 3 variable salinity, the effects of salinity on population dynamics are poorly understood. We used existing 4 literature to parameterize salinity-dependent logistic mortality curves for different life stages of sea lice. 5We then used population matrix models to characterize the effects of temperature and salinity on sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Since most marine finfish aquaculture occurs within the coastal zone, salinity and temperature regimens can be dynamic (Groner et al, 2016). Salinity near salmon farms is influenced by fresh water inflow from rivers and precipitation, coastal and oceanic water exchange, mixing of the water column (due to wind and tides), estuarine circulation, and inlet bathymetry.…”
Section: Introductionmentioning
confidence: 99%
“…Since most marine finfish aquaculture occurs within the coastal zone, salinity and temperature regimens can be dynamic (Groner et al, 2016). Salinity near salmon farms is influenced by fresh water inflow from rivers and precipitation, coastal and oceanic water exchange, mixing of the water column (due to wind and tides), estuarine circulation, and inlet bathymetry.…”
Section: Introductionmentioning
confidence: 99%
“…Changing salinity may even control certain disease outbreaks. A relative reduction in salinity may control infections as such as Dermo disease in oysters (Burge et al 2014) and sea lice on salmon (Groner et al 2016), whereas a relative increase in salinity has been reported to control certain infections such as V. vulnificus in hybrid tilapia (Oreochromis sp.) (Chen et al 2006) and to decrease infection with the parasitic nematode Anguillicoloides (= Anguillicola) crassus in Atlantic eels (Anguilla spp.)…”
Section: Water Qualitymentioning
confidence: 99%
“…When real production data has been used for estimation, these have been aggregated. For instance, Stien et al (2005) used only laboratory data published in previous papers, whereas Groner et al (2013) and Groner et al (2016) used values from Stien et al (2005) for some parameters and values from several other previous papers for other parameters. Furthermore, Revie et al (2005) and Gettinby et al (2011) used laboratory data from previous studies to estimate the majority of the parameters and real production data to estimate the remaining parameters, but the production data were aggregated over farms and to a monthly time scale.…”
Section: Modelling Backgroundmentioning
confidence: 99%
“…Alternatively, models have been developed for simulation purposes only (Groner et al, 2014) or focused on the population dynamics on single farms over a limited time period (Krkošek et al, 2010). Most of these approaches have relied heavily on estimates of demographic rates ob-tained in the laboratory (Stien et al, 2005;Revie et al, 2005;Gettinby et al, 2011;Groner et al, 2013;Rittenhouse et al, 2016;Groner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%